Life Cycle, Ultrastructure, and Phylogeny of New Diplonemids and Their Endosymbiotic Bacteria - Tashyreva, Daria; Prokopchuk, Galina; Votýpka, Jan; Yabuki, Akinori; Horák, Aleš; Lukeš, Julius (mBio, 2018)
Diplonemids represent a hyperdiverse and abundant yet poorly studied group of marine protists. Here we describe two new members of the genus Diplonema (Diplonemea, Euglenozoa), Diplonema japonicum sp. nov. and Diplonema aggregatum sp. nov., based on life cycle, morphology, and 18S rRNA gene sequences. Along with euglenozoan apomorphies, they contain several unique features. Their life cycle is complex, consisting of a trophic stage that is, following the depletion of nutrients, transformed into a sessile stage and subsequently into a swimming stage. The latter two stages are characterized by the presence of tubular extrusomes and the emergence of a paraflagellar rod, the supportive structure of the flagellum, which is prominently lacking in the trophic stage. These two stages also differ dramatically in motility and flagellar size. Both diplonemid species host endosymbiotic bacteria that are closely related to each other and constitute a novel branch within Holosporales, for which a new genus, "Candidatus Cytomitobacter" gen. nov., has been established. Remarkably, the number of endosymbionts in the cytoplasm varies significantly, as does their localization within the cell, where they seem to penetrate the mitochondrion, a rare occurrence.IMPORTANCE We describe the morphology, behavior, and life cycle of two new Diplonema species that established a relationship with two Holospora-like bacteria in the first report of an endosymbiosis in diplonemids. Both endosymbionts reside in the cytoplasm and the mitochondrion, which establishes an extremely rare case. Within their life cycle, the diplonemids undergo transformation from a trophic to a sessile and eventually a highly motile swimming stage. These stages differ in several features, such as the presence or absence of tubular extrusomes and a paraflagellar rod, along with the length of the flagella. These morphological and behavioral interstage differences possibly reflect distinct functions in dispersion and invasion of the host and/or prey and may provide novel insight into the virtually unknown function of diplonemids in the oceanic ecosystem.
Keywords: Symbiosis; stadia vývoje; Life Cycle Stages; Meiotic Prophase I; diplonemid; Bacteria; RNA, Ribosomal, 18S; ultrastructure; life cycle; RNA ribozomální 18S; symbióza; Phylogeny; Holosporales; fylogeneze; profáze meiózy I; endosymbionts